Introduction to classical & New Testament Greek a unified approach - Boler, Michael (Washington, D.C The Catholic Education Press, 2020)
The defining feature of this textbook is the treatment of classical and New Testament Greek as one language using primary sources. All the example sentences the students will translate are real Greek sentences, half of which are taken from classical literature and philosophy and half of which are directly from the New Testament. The advantage of this approach is that it highlights the linguistic, literary, and historical connections between classical Greece and early Christianity. Rather than having students memorize isolated tables and artificial sentences, Michael Boler spent years combing through thousands of pages of literature, philosophy, and scripture to find short, powerful sentences that not only teach the grammatical concepts in each chapter, but also contain seeds of wisdom that will spark wonder and discussion. Introduction to New Testament and Classical Greek is born out of classroom experience in a Catholic liberal arts university whose students were disappointed to be forced to choose between textbooks that taught classical Greek in isolation and ones that focused exclusively on the New Testament. By the end of this book, students will have read over 200 lines of scripture and an equal amount of ancient literature from Homer to Aristotle. They will also have the grammatical knowledge to continue to read classical and New Testament Greek. Each chapter contains a section at the end that delves deeply into the etymology and background of the words and passages encountered in the respective chapter. Professors will thus be able to use these chapters as a bridge to philosophical, theological, historical, and literary topics that will enrich the class
Keywords: Bible -- Language, style; Greek language, Biblical -- Grammar; Greek language, Biblical; Greek language, Biblical ; Grammar; Textbooks; Einführung